2018
DOI: 10.1002/1873-3468.13019
|View full text |Cite
|
Sign up to set email alerts
|

Active site alanine preceding catalytic cysteine determines unique substrate specificity in bacterial CoA‐acylating prenal dehydrogenase

Abstract: In detoxification and fermentation processes, acylating dehydrogenases catalyze the reversible oxidation of aldehydes to their corresponding acyl-CoA esters. Here, we characterize an enzyme from Aquincola tertiaricarbonis L108 responsible for prenal (3-methyl-2-butenal) to 3-methylcrotonyl-CoA oxidation. Enzyme kinetics demonstrate a preference for C5 substrates not yet observed in aldehyde dehydrogenases. Compared to acetaldehyde and acetyl-CoA, conversion of valeraldehyde and valeryl-CoA is > 100- and 8-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Trace concentration of crotyl diphosphate was detected, and 0.51 μg/mL of crotonol (7.0 μM) was produced at 4 h. This result indicated that low activity of ADHE2 was one major bottleneck resulting in the lack of reduction of crotonyl-CoA into crotyl alcohol. Just recently, Becher et al characterized a novel CoA-acylating aldehyde dehydrogenase responsible for prenal (3-methyl-2-butenal) to 3-methylcrotonyl-CoA oxidation [48], which could possibly improve the activity for the first step of reduction of crotyl-CoA to crotonaldehyde. Future direction will be focused on improving catalytic efficiency of crotyl-CoA into crotyl alcohol to realize the production of butadiene precursor from methanol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trace concentration of crotyl diphosphate was detected, and 0.51 μg/mL of crotonol (7.0 μM) was produced at 4 h. This result indicated that low activity of ADHE2 was one major bottleneck resulting in the lack of reduction of crotonyl-CoA into crotyl alcohol. Just recently, Becher et al characterized a novel CoA-acylating aldehyde dehydrogenase responsible for prenal (3-methyl-2-butenal) to 3-methylcrotonyl-CoA oxidation [48], which could possibly improve the activity for the first step of reduction of crotyl-CoA to crotonaldehyde. Future direction will be focused on improving catalytic efficiency of crotyl-CoA into crotyl alcohol to realize the production of butadiene precursor from methanol.…”
Section: Resultsmentioning
confidence: 99%
“…This was likely because of low activity of ADHE2 towards crotonyl-CoA reduction. In the future, it should be possible to address this issue including protein design and manipulating the flux through the EMC pathway [14, 48, 49]. Although further enzymes and strain optimization are required to make this system industrially relevant, this novel work is the first example for biosynthesis of butadiene precursors.…”
Section: Discussionmentioning
confidence: 99%
“…In DSM 45062 cultures, consumption of substrates and formation of metabolites were routinely monitored by HPLC (Shimadzu Corporation) equipped with a Hi-Plex H column (300 mm × 7.7 mm; Agilent Technologies) and refractive index detector (Becher et al, 2018). In addition, acetone was quantified by headspace GC (Agilent Technologies) employing an Optima Delta-3 column (60 m × 0.32 mm × 0.25 µm; Macherey-Nagel) and flame ionization detection (Becher et al, 2018).…”
Section: Analyticsmentioning
confidence: 99%
“…In DSM 45062 cultures, consumption of substrates and formation of metabolites were routinely monitored by HPLC (Shimadzu Corporation) equipped with a Hi-Plex H column (300 mm × 7.7 mm; Agilent Technologies) and refractive index detector (Becher et al, 2018). In addition, acetone was quantified by headspace GC (Agilent Technologies) employing an Optima Delta-3 column (60 m × 0.32 mm × 0.25 µm; Macherey-Nagel) and flame ionization detection (Becher et al, 2018). Formation of ketones in bacterial cultures and in the lyase assays was verified by a GC system (Agilent Technologies) equipped with an Optima Delta-3 column (30 m × 0.25 mm × 0.25 µm; Macherey-Nagel) and mass spectrometer (Becher et al, 2018).…”
Section: Analyticsmentioning
confidence: 99%
See 1 more Smart Citation